Alternative RNA splicing generates diversity of neuropeptide expression in the brain of the snail Lymnaea: in situ analysis of mutually exclusive transcripts of the FMRFamide gene - Santama, N; Benjamin, P R; Burke, J F (The European journal of neuroscience, 1995)
In the CNS of the snail Lymnaea stagnalis, Phe-Met-Arg-Phe-amide (FMRFamide)-like and additional novel neuropeptides are encoded by a common, multi-exon gene. This complex locus, comprising at least five exons, is subject to post-transcriptional regulation at the level of alternative RNA splicing. Our aim was first to analyse the pattern by which exons of this neuropeptide locus combine during splicing of the primary RNA transcript, and second to investigate the functional significance of splicing by mapping the expression and neuronal localization in the CNS of the alternative mRNA transcripts, in the context of defined neuronal networks and single identified neurons. The approach was a combination of comparative in situ hybridization and immunocytochemistry, using a battery of exon-specific oligonucleotides and anti-peptide antisera. The analysis illustrated that exons III, IV and V were always coexpressed and colocalized whereas the expression of exon II was always differential and mutually exclusive. Both sets of exons were, however, coexpressed with exon I: the total number of exon I-expressing neurons was equal to the combined number of neurons expressing exon III/IV/V and neurons expressing exon II. In addition, it was revealed that the extreme 5' of exon II, encoding a potential hydrophobic leader signal, was not expressed in the CNS of Lymnaea but was apparently spliced out during RNA processing. Both mRNA transcripts of the FMRFamide locus, type 1 (exons I/II) and type 2 (exons I/III/IV/V), were translated in the CNS and the resulting protein precursors were also expressed in a mutually exclusive fashion, as were their respective transcripts. The expression of alternative transcripts within identified networks or neuronal clusters was heterogeneous, as exemplified by the cardiorespiratory network. On the basis of this work and a previous cDNA analysis, we put forward a revised model of differential splicing and expression of the FMRFamide gene in the CNS of Lymnaea.